AI-Assisted Research Mentoring in Graduate Thesis Writing: A Reflective Inquiry on the Use of ChatGPT - Jay L. Galimpin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This reflective inquiry examined how ChatGPT facilitated the author’s graduate thesis-writing journey as an AI-assisted mentor, co-thinking partner, and writing support tool. Anchored on a scholarly reflective inquiry design, the article drew from the researcher’s lived experience in developing a thesis on theory-based metacognitive instructional design in mathematics education. Reflective data were gathered from the researcher’s thesis-writing experiences, AI-assisted interactions, manuscript revisions, defense preparation, and personal realizations throughout the research process. Thematic reflective analysis showed that ChatGPT supported conceptual clarification, methodological organization, scholarly writing, results alignment, and defense preparation. More importantly, AI interaction prompted the researcher to monitor understanding, regulate revisions, question uncertain outputs, and evaluate suggestions against theoretical, methodological, and scholarly evidence. However, the inquiry also emphasized that ChatGPT remained a fallible tool requiring source verification, numerical checking, human revision, adviser guidance, and researcher accountability. The study concludes that ChatGPT may serve as a meaningful AI-assisted research mentor when used critically, transparently, and ethically. Its strongest contribution lies not in replacing scholarly work, but in helping the researcher think more clearly, write more coherently, and develop greater confidence in the research process.